Stakeholders Prioritization Framework of Climate-Smart Agriculture Interventions - CGIAR Research Program on Climate Change, Agriculture and Food Security (2018)
The climate smart agriculture prioritization framework is developed and evaluated across the climate smart village sites in India and Nepal. This framework is being usede to develop portfolio of CSA intervention in Climate-Smart Village (CSV) program in many agro-ecological zones of South Asia.